2020
DOI: 10.1101/2020.04.04.023945
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective activation of Gαob by an adenosine A1 receptor agonist elicits analgesia without cardiorespiratory depression

Abstract: One third of all medicines act at G protein-coupled receptors (GPCRs). However, the identification of new therapeutic GPCR targets is limited by a fundamental property of GPCRs: their propensity to couple to different G protein alpha subunits (Gα) leading to multiple downstream cellular effects. This is especially the case for adenosine A1 receptors (A1Rs), the activation of which results in unwanted cardiorespiratory effects, severely limiting their clinical potential. We have discovered that the novel A1R ag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 159 publications
0
4
0
Order By: Relevance
“…VCP746 showed bias towards the cAMP pathway relative to (probably G protein-dependent 74,75 ) ERK1/2 signalling, and no observable effect on heart rate in isolated rat atria 33 . SAR studies 33,76 determined that the 3-(trifluoromethyl)phenyl substituent is important for the allostericallydriven A 1 R bias, while the best linker length between the two pharmacophores (Figure 1) is six carbon atoms.…”
Section: Exploring the Bitopic Ligand Vcp476 Binding Modementioning
confidence: 89%
“…VCP746 showed bias towards the cAMP pathway relative to (probably G protein-dependent 74,75 ) ERK1/2 signalling, and no observable effect on heart rate in isolated rat atria 33 . SAR studies 33,76 determined that the 3-(trifluoromethyl)phenyl substituent is important for the allostericallydriven A 1 R bias, while the best linker length between the two pharmacophores (Figure 1) is six carbon atoms.…”
Section: Exploring the Bitopic Ligand Vcp476 Binding Modementioning
confidence: 89%
“…However, in most cases, the precise G protein-dependent or independent pathways involved in the salutary effects of adenosine agonists are unexplored. Recently, an A 1 AR agonist that was reported to selectively activate G ob versus the other five G α i/o subtypes and without β -arrestin recruitment was discovered ( Wall et al, 2020 ). It appears to act as a potent analgesic without sedation or cardiorespiratory depression.…”
Section: Discussionmentioning
confidence: 99%
“…The AR biased agonism has been explored by MD simulations. By combining MD simulations, Gαi/o subunit- and β-arrestin-specific cellular signaling assays, Wall et al [ 106 ] identified that the A 1 AR-selective agonist, BnOCPA, was a biased agonist in exclusively activating the G ob protein. MD simulations were applied on the A 1 AR bound by the biased agonist BnOCPA, neutral agonists ADO and HOCPA and an antagonist PSB36.…”
Section: Molecular Simulations Revealed Functional Mechanisms Of Aden...mentioning
confidence: 99%
“…Wall et al [ 106 ] discovered biased agonist BnOCPA of A 1 AR that favors G ob over other G protein subtypes and hence produces analgesic effects without sedation, bradycardia and hypotension. MD simulations revealed the BnOCPA binding modes in the receptor.…”
Section: Computer-aided Drug Discovery Of Adenosine Receptorsmentioning
confidence: 99%